2015
DOI: 10.1063/1.4928560
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing design of irradiation uniformity of direct drive cone-in-shell target for fast ignition

Abstract: The irradiation uniformity of a cone-in-shell target directly driven by laser beams has been considered. First, a model is established to include the influence of the cone on laser beam propagation. Then, the irradiation uniformity on the target surface outside the cone during the initial imprinting phase is analyzed, and highly uniform irradiation on the target surface outside the cone is achieved by optimizing the intensity distribution within laser beams, as well as the polar direct drive displacement. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Computational and theoretical studies in this area are carried out for targets of various designs and different approaches to ignition. Many important results of these studies relating to direct-drive ignition using modern laser facilities can be found in [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The problem statement itself depends on the target irradiation geometry with a specific laser facility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computational and theoretical studies in this area are carried out for targets of various designs and different approaches to ignition. Many important results of these studies relating to direct-drive ignition using modern laser facilities can be found in [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The problem statement itself depends on the target irradiation geometry with a specific laser facility.…”
Section: Introductionmentioning
confidence: 99%
“…Using such beam configurations for directdrive schemes, also known as polar-direct-drive (PDD), greatly impairs the irradiation uniformity. Parts of the studies deal with the specifics of shock ignition [32,[35][36][37] and fast ignition [38,39,42]. The recently published papers [40,41] are directly related to the direct-drive spark-ignited targets in the spherical symmetric geometry of laser beam irradiation.…”
Section: Introductionmentioning
confidence: 99%